Boosting effect of regular sport practice in young adults: Preliminary results on cognitive and emotional abilities - Passarello, Noemi; Varini, Ludovica; Liparoti, Marianna; Troisi Lopez, Emahnuel; Sorrentino, Pierpaolo; Alivernini, Fabio; Gigliotta, Onofrio; Lucidi, Fabio; Mandolesi, Laura (Frontiers in Psychology, 2022)
Several studies have been shown that Physical Exercise (PE) improves behavior and cognitive functioning, reducing the risk of various neurological diseases, protecting the brain from the detrimental effects of aging, facilitating body recovery after injuries, and enhancing self-efficacy and self-esteem. It is also widely agreed that emotion processing is an integral component of success in sport practice. In this study, we aim to demonstrate that regular participation in sports can lead to improved cognitive and emotional functioning among individuals. A sample of 60 students (mean age = 22.12; SD = 2.40; M = 30), divided into sportive and sedentary, were subjected to a battery of neuropsychological tests to assess their overall cognitive abilities (Raven's Advanced Progressive Matrices, APM), verbal and graphic fluency (Word Fluency Task and modified Five Point Test, m-FPT), as well as their emotional awareness skills (Toronto Alexithymia Scale, TAS-20). We found a better performance of sportive in comparison to sedentary in all cognitive tasks. Interestingly, significant differences were found in TAS-20 total score as well as in Difficulty Describing Feelings subscale (DDF) and Difficulty Identifying Feeling subscale (DIF). Lastly gender differences were found in Externally Oriented Thinking subscale (EOT). Overall, our results evidence that PE has positive effects on cognitive functioning and emotion regulation, suggesting how sports practice can promote mental health and well-being.